Efeitos da dieta hiperproteica na ansiedade, na hemodinâmica e em aspectos morfofuncionais do coração de ratos wistar - Souza, Flander Diego (2020)
Introduction: Anxiety is a preparatory response mechanism to situations of threat and danger, involving behavioral, cognitive, physiological and affective factors. Anxious individuals believe that the likelihood of negative events occurring is very high, feeling threatened and reacting in the wrong way. In 2017, WHO published research showing that Brazil leads, among all countries, in terms of the prevalence of anxiety disorders. The complex pathogenesis of anxiety is mediated by several neurotransmitters. Glutamate, as an excitatory amino acid of the CNS, has the function of protecting the animal and protecting it from any imminent danger. It is an abundant amino acid in the diet, being found largely in foods of animal origin. The use of high protein diet has been gaining popularity in recent years, being used as a dietary strategy to promote body weight reduction in overweight and obese individuals, and studies have shown beneficial effects on muscle mass and cardiovascular health. Objective: To investigate the relationship of diet with high protein content in anxiety and in morphofunctional and cardiovascular aspects of Wistar rats. Material and Methods: The experiment was carried out at the Rodent Animal Bioterium Network of the Federal University of Uberlândia (REBIRUFU) and lasted eight weeks. Twenty-nine male Wistar rats were used, with an average weight between 250-300g, divided into two groups, one with a standard normoproteic diet (C = 14 animals) and another with a high protein diet (H = 15 animals). Anxiety was assessed by the elevated plus-maze test (CSF) and cardiovascular aspects by invasive hemodynamic measurements and transthoracic echocardiography. For comparisons between groups, Student's t-test or analysis of variance (ANOVA) was used, followed, when necessary, by the Tukey test. Statistical significance was established for p values ≤ 0.05. Results: There was no statistically significant difference in the anxiety test, however, the hyperproteic group was more agitated with a greater displacement during the test. Significantly less morphofunctional changes were found in the group that received the high-protein diet: final stroke volume and final diastolic volume, left ventricular diameter in systole and heart rate. The thickness of the interventricular septum in diastole was greater in the hyperprotein group. No hemodynamic changes were observed. Conclusion: The high protein diet had no influence on anxiety but induced morphofunctional adaptations in the heart, suggesting less cardiac work.